Hybrid fibre reinforced ultra-high performance concrete beams under static and impact loads. (15th October 2021) - Wei, Jie; Li, Jun; Wu, Chengqing; Liu, Zhong-xian; Li, Jie
Highlights: Hybrid fibre reinforced UHPC showed higher flexural strength. Tensile softening curves was developed by inverse analysis, hybrid fibre reinforced UHPC showed higher fracture energy. Impact resistance of UHPC beam subjected to single and multiple impacts were investigated. Hybrid fibre reinforced UHPC beams showed better impact resistance. Abstract: High mechanical strength and ductility of fibre reinforced ultra-high performance concrete (UHPC) are beneficial to its loading capacity under static and dynamic loads. To further improve the material performance, especially the crack restraint capability and flexural capacity, hybrid fibre reinforcement in UHPC is investigated in the present study. This study first investigated the influence of hybrid straight steel fibres on the static mechanical performance of UHPC. Four mixtures with single and hybrid fibre reinforcement were developed. Fibres with three different lengths (6, 10, 15 mm) but identical diameter (0.2 mm) and volume dosage (2.5%) were incorporated. Quasi-static compression and flexural tests were conducted on these mixtures. The findings in this study indicated that while longer fibre provided an improvement of both compressive strength and elastic modulus, UHPC with hybrid fibres demonstrated better flexural performance. With notched three-point bending test results, tensile softening curves and fracture energy of UHPC were obtained and discussed. The flexural strength and fracture energy of mixture with hybrid long and short fibre was 21.84% and 20.13% greater than those with single long fibre reinforcement. Subsequently, the dynamic behaviour of UHPC beams (2000 × 168 × 168 mm) with a single and hybrid fibre reinforcement was investigated against low-velocity impact. The impact scenario was modelled with 641 kg drop hammer falling freely to the mid-span of the UHPC beams. The test results showed all specimens exhibited flexural response with minimal damage. The impact resistance of UHPC beams reinforced with hybrid fibres was found better than that with single long fibre reinforcement. The maximum and residual displacement of the mixture with hybrid long and medium fibre was 16.08% and 23.95% lower than that with long fibre reinforcement.